The molecular profile of adult T‐cell acute lymphoblastic leukemia: Mutations in RUNX1 and DNMT3A are associated with poor prognosis in T‐ALL. Issue 4 (23rd January 2013) - Grossmann, Vera; Haferlach, Claudia; Weissmann, Sandra; Roller, Andreas; Schindela, Sonja; Poetzinger, Franziska; Stadler, Kathrin; Bellos, Frauke; Kern, Wolfgang; Haferlach, Torsten; Schnittger, Susanne; Kohlmann, Alexander
Abstract T‐cell acute lymphoblastic leukemia (T‐ALL) is an aggressive and heterogeneous disease. The diagnosis is predominantly based on immunophenotyping. In addition to known cytogenetic abnormalities molecular mutations were recently identified. Here, 90 adult T‐ALL cases were investigated for mutations in NOTCH1, FBXW7, PHF6, CDKN2A, DNMT3A, FLT3, PTEN, and RUNX1 using 454 next‐generation amplicon sequencing and melting curve analyses. These data were further complemented by FISH, chromosome banding, array CGH, and CDKN2B promoter methylation analyses. NOTCH1 was the most frequently mutated gene with a 71.1% frequency followed by FBXW7 (18.9%), PHF6 (39.5%), DNMT3A (17.8%), RUNX1 (15.5%), PTEN (10.0%), CDKN2A (4.4%), FLT3‐ITD (2.2%), and FLT3‐TKD (1.1%). In total, 84/90 (93.3%) cases harbored at least one mutation. Combining these data with CDKN2A/B deletions and CDKN2B methylation status, we detected minimum one aberration in 89/90 (98.9%) patients. Survival analyses revealed the subtype as defined by the immunophenotype as the strongest independent prognostic factor. When restricting the survival analysis to the early T‐ALL subtype, a strong association of RUNX1 (P = 0.027) and DNMT3A (P = 0.005) mutations with shorter overall survival was observed. In conclusion, RUNX1 and DNMT3A are frequently mutated in T‐ALL and are associated with poor prognosis in early T‐ALL. © 2013 Wiley Periodicals, Inc.